COMMUNITY EMPOWERMENT ON UTILIZATIONHUSK WASTE INTO HUSK CHARCOAL BRIQUETTES - Kesmayanti, Novisrayani Kesmayanti; Ilmi, Bahrul Ilmi (Universitas Djuanda, 2022)
The land characteristics of Pemulutan Ilir Village are dominated by swamps, so the people's main agriculture is the cultivation of lowland swamp rice. The existence of extensive rice fields encourages the development of rice milling businesses that produce husk waste. The husk waste has not been utilized by the community. If processed, rice husk waste will become a more useful product, once is husk charcoal briquettes. This community service activity is the implementation of the Community Partnership Program of the Ministry of Education and Culture of the Republic of Indonesia in 2022 which is carried out by the IBA University team. The participants are the community of Pemulutan Ilir Village. Activities start from May-December 2022. Activities are carried out in several stages, starting with surveys and field observations to inventory and analyze partner resources and problems, determine problem solutions, conduct training and mentoring partners to utilize husk waste into charcoal biobriquettes. To the community, there has been a transfer of technological innovation for making husk charcoal briquettes, training and assistance in the process of burning to produce husk charcoal, making adhesive dough, briquette dough and printing briquettes. The result is the peoples of Pemulutan Ilir Village have succeeded in absorbing and being able to carry out all stages for making husk charcoal briquettes and have succeeded in making husk charcoal briquettes that are dense, neat and uniform. The community is very motivated to produce husk charcoal briquettes commercially in order to increase their income and improve the family's economy